1985
DOI: 10.1111/j.1365-3032.1985.tb00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Phonotaxis and aggression in the coneheaded katydid Neoconocephalus affinis

Abstract: ABSTRACT. Positive phonotaxis to tape recorded conspecific song by males of the katydid Neoconocephalus affinis (Beauvois) (Orthoptera: Tettigoniidae) was studied in the field, in Puerto Rico. N.affinis males stridulated loudly during evening hours, and most males were territorial. Aggression between neighbours occurred, albeit rarely, and playback experiments using tape recordings of N.affinis song showed that aggressive behaviour, in the form of jumps directed toward a loudspeaker, could be elicited from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This view may be particularly valid for alternated signals. It is indicated by the role of acoustic signaling in spacing (5,12) and aggression (61,143,157) and by the difficulties that animal may have in perceiving a neighbor's calls during its own signaling. Evidence for the latter comes both from behavioral experiments relying on the technique of interactive playback (see 34, 126) and from neurophysiological investigation.…”
Section: Mutual Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This view may be particularly valid for alternated signals. It is indicated by the role of acoustic signaling in spacing (5,12) and aggression (61,143,157) and by the difficulties that animal may have in perceiving a neighbor's calls during its own signaling. Evidence for the latter comes both from behavioral experiments relying on the technique of interactive playback (see 34, 126) and from neurophysiological investigation.…”
Section: Mutual Assessmentmentioning
confidence: 99%
“…INCOMPATIBILITY OF SIGNALING AND PERCEPTION Sexually advertising males in many acoustic orthopteran and anuran species space themselves regularly or maintain minimum nearest-neighbor distances via mutual assessment of calls (5,12,105). In some acoustic species hearing is reduced during calling, a handicap due either to simple masking (69) or to neural (154) or biomechanical (107) devices.…”
Section: Mutual Assessmentmentioning
confidence: 99%
“…Brush et al (1985) demonstrated positive phonotaxis for males of the bush cricket Neoconocephalus affinis. Mygalopsis marki responds to the conspecific song by climbing down the stem of the plant and by changing the chirp rate (Dadour and Bailey, 1985).…”
Section: Discussionmentioning
confidence: 97%
“…Downloaded by [141.214.17.222] at 04:21 01 November 2014 298 A. Schatral and W. Latimer Sound intensity has been found to be involved in male spacing and male competition (Thiele and Bailey, 1980;Schatral et al, 1985;Brush et al, 1985;Dadour and Bailey, 1985). The dominant frequency peak of the song is an important cue used in competitive interactions in Tettigonia cantans .…”
Section: Introductionmentioning
confidence: 97%
“…Males aggregate in patches of taller vegetation, but within such patches maintain regular interindividual distances by physical and acoustical interactions with their neighbours (see also Brush et al 1985;Schatral et al 1985). The acoustic cues males use to maintain spacing probably include the relative harmonic content of songs as well as the absolute intensity (Keuper et al 1986;Latimer and Lewis 1986;R6mer and Bailey 1986;R6mer 1987;Simmons 1988).…”
Section: Behavioural Adaptations Of Singing Malesmentioning
confidence: 99%